Implementation of basic education data system (dapodik) management in student data management in early childhood education - Dwi Winarsih; Tri Yuni Hendrowati; Fatqul Hajar Aswad (Indonesian Journal Education, 2026)
This study investigates the implementation of the Basic Education Data System (DAPODIK) in student data management at TK Al Hidayah Tanjung Jaya, an early childhood education institution in Indonesia. Using a qualitative descriptive case study approach, data were collected through observations, in-depth interviews, and documentation involving the principal, DAPODIK operator, and teachers. The findings reveal that DAPODIK management has been implemented through four core management functions: planning, organizing, implementation, and supervision. Planning includes assigning responsible personnel and scheduling data collection, while organizing emphasizes collaboration among school stakeholders despite the operator’s multiple administrative responsibilities. The implementation process involves routine data entry, updating, and synchronization but is constrained by incomplete parental documentation, limited operator technical competence, inadequate technological facilities, and unstable internet connectivity. Furthermore, supervision and data quality evaluation are conducted only on an incidental basis and lack a structured monitoring mechanism. The study concludes that although DAPODIK has supported student data management, its implementation remains suboptimal. Strengthening human resource capacity, establishing comprehensive standard operating procedures, improving task distribution, and enhancing technological infrastructure are recommended to improve the effectiveness and reliability of education data management in early childhood education institutions.